Systemakkreditierung an Hochschulen Anforderungen, Maßnahmen und Effekte aus der Perspektive von Hochschulakteuren - Suwalski, Petra (Verlag Barbara Budrich, 2020)
The empirical study examines dynamic change processes that occur when introducing system accreditation from the perspective of university management and those responsible for quality management. Challenges, action practices and coping strategies of the change actors as well as the effects of system accreditation are identified and theoretical and practical implications for the design of university development processes are shown.